Effects of a nurse-led medication self-management programme in women with oral treatments for metastatic breast cancer: A mixed-method randomised controlled trial. (August 2020) - Komatsu, Hiroko; Yagasaki, Kaori; Yamaguchi, Takuhiro; Mori, Ayako; Kawano, Hiromi; Minamoto, Noriko; Honma, Orie; Tamura, Kenji
Abstract: Purpose: Adherence to medication is the most important challenge facing patients receiving oral anticancer treatment. This study aimed to evaluate the effects of a patient-centred medication self-management support programme in patients with metastatic breast cancer undergoing oral anticancer treatment. Methods: This trial was a two-phased mixed-method randomised controlled study. Eligible participants were 155 patients with metastatic breast cancer newly prescribed an oral chemotherapy or targeted therapy agent. The intervention group received the patient-centred medication self-management support programme conducted by trained nurses. Primary outcome was adherence to medication at three months after the commencement of treatment, calculated by medication possession ratio (MPR). Secondary outcomes included self-efficacy, functional assessment, psychological distress, symptom severity and symptom interference, and patient satisfaction. After the completion of the intervention study, focus group interviews were conducted among intervention nurses. Results: Both intervention and control groups maintained more than 90% of MPR and no significant difference was observed in the primary outcome. Regarding secondary outcomes, only general self-efficacy was significantly different in the two groups. In the qualitative study, the intervention nurses perceived improvement in the patients' self-efficacy, ability to anticipate the impact of treatment and adjust to life, and avoidance of loneliness. Conclusions: A significant effect of the programme was not found in the program because the adherence rate was high in both groups. Improvement in the patients' self-efficacy was observed both quantitatively and qualitatively. Trial Registration: UMIN Clinical Trials Registry (UMIN-CTR), Japan, UMIN000016597. (27 February 2015). Highlights: A self-management support programme was evaluated in women undergoing oral anticancer treatment. We found no difference in adherence but did find improvements in self-efficacy. Future studies need to clarify the over-adherence issue and the effect of self-efficacy.